Transcriptome analysis of novel B16 melanoma metastatic variants generated by serial intracarotid artery injection - Jenny C. Kienzler; Erick M. Contreras; Janet Treger; Linda M. Liau; Geoffrey C. Owens; Robert M. Prins (Acta Neuropathologica Communications)
Abstract The incidence of brain metastases (BrM) in patients with metastatic melanoma is reported to be 30–50% and constitutes the third most frequent BrM after breast and renal cancers. Treatment strategies including surgical resection, stereotactic radiation, and immunotherapy have improved clinical response rates and overall survival, but the changes that occur in circulating melanoma cells to promote invasion of the brain are not fully understood. To investigate brain tropism, we generated new variants of the B16 mouse melanoma model by serially passaging B16 cells through the brain of immune competent syngeneic C57BL/6 mice. Cells were injected into the right carotid artery and recovered from the brain after the mice had reached the study endpoint due to tumor burden, then expanded in vitro and reinjected. We compared the transcriptomes of 4th generation B16 cell populations from separate lineages with the founder B16-F0 cells. Gene set enrichment analysis (GSEA) of differentially expressed protein coding genes revealed that cells isolated from the brain as well as from the lung and meninges expressed higher levels of genes associated with an epithelial to mesenchymal transition (EMT), upregulation of the KRAS signaling pathway, and a metastasis aggressiveness gene signature associated with poor survival in melanoma patients. Principal component analysis of differentially expressed genes showed that 4th generation melanoma cells isolated from the brain, lung and meninges from one lineage were distinct from those of the other three lineages. Among the differentially expressed genes, transcript levels of several genes, including Itgb2, Rftn2, and Kcnn4, were significantly higher in all cell populations that comprised this lineage compared with all cell populations from the other three lineages. In conclusion, we have derived an aggressive, highly brain metastatic B16 variant associated with leptomeningeal disease by serially passaging cells in vivo.